AN INFLUENCE OF MANAGEMENT INTELLIGENCE AND EMOTIONAL INTELLIGENCE ON THE PERFORMANCE OF CIVIL SERVANTS (PNS). - Daulay, Akman; Surbakti, Syamsul Bahri; Sinto, Sinto (Jurnal Ekonomi, 2022)
The Binjai Resort Police (Polres) is one of the state institutions that handles public security issues under the North Sumatra Regional Police (POLDASU), in carrying out their services the police officers are assisted by their civil servants or Civil Servants who are assigned to assist in handling service administration the public at the police station. The results showed that: The variable of spiritual intelligence is the value of tcount- 1,820 > ttable1,692 with a significant 0.000 <0.050, meaning that partially Spiritual Intelligence has a positive and significant effect on Employee Performance, it can be concluded that hypothesis 1 is accepted. Emotional Intelligence variable value tcount10.460 > ttable1,692 with a significant 0.000 > 0.050, meaning that partially there is influence and significant from Emotional Intelligence on Employee Performance, it can be concluded that hypothesis 1 is accepted. Based on the results of the determination test, the adjusted R square is 0.964, this means that 96.4% of employee performance variations can be explained by the independent variables Spiritual Intelligence and Emotional Intelligence, while the rest (100% - 96.4% = 5.6%) can be explained by other independent variables that are not included. include in this research such as leadership style, work environment and others.